2012
DOI: 10.1182/blood.v120.21.1628.1628
|View full text |Cite
|
Sign up to set email alerts
|

Short Cycle of Immunochemotherapy Followed by Radiation Therapy Compared with Prolonged Cycles of Immunochemotherapy for Localized DLBCL: The Osaka Lymphoma Study Group (OLSG) Retrospective Analysis

Abstract: 1628 Introduction: Standard treatment for localized diffuse large B cell lymphoma (DLBCL) has been rather a short cycle of immunochemotherapy followed by involved field radiotherapy or prolonged cycles of immunochemotherapy. There is no convincing evidence in favor of either strategy. This retrospective analysis is an attempt to compare these treatment options. Methods: Patients were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A matched pair analysis was performed to control for potential confounders and showed an improvement in OS and PFS with combined modality therapy versus chemotherapy alone, however, this matched pair analysis was limited by a small sample size and probably wide confidence intervals for hazard ratio estimates (44 matched pairs), selection bias inherent in subset analysis and matching on only three factors [disease bulk (>5 cm), response to therapy (defined as resolution of original tumours) and IPI score]. In contrast, other retrospective analyses reported no significant differences in outcome for 6-8 cycles of R-CHOP chemotherapy alone versus 3-4 cycles of R-CHOP followed by IFRT (Terada et al, 2012;Odejide et al, 2015). One study was a large retrospective Surveillance, Epidemiology, and End Results Program database analysis comparing treatment with 3-4 cycles of R-CHOP plus RT to 6-8 cycles of R-CHOP in 874 elderly (>65 years) patients with DLBCL, and showed no difference in OS using propensity-score weighted Cox regression models (Odejide et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A matched pair analysis was performed to control for potential confounders and showed an improvement in OS and PFS with combined modality therapy versus chemotherapy alone, however, this matched pair analysis was limited by a small sample size and probably wide confidence intervals for hazard ratio estimates (44 matched pairs), selection bias inherent in subset analysis and matching on only three factors [disease bulk (>5 cm), response to therapy (defined as resolution of original tumours) and IPI score]. In contrast, other retrospective analyses reported no significant differences in outcome for 6-8 cycles of R-CHOP chemotherapy alone versus 3-4 cycles of R-CHOP followed by IFRT (Terada et al, 2012;Odejide et al, 2015). One study was a large retrospective Surveillance, Epidemiology, and End Results Program database analysis comparing treatment with 3-4 cycles of R-CHOP plus RT to 6-8 cycles of R-CHOP in 874 elderly (>65 years) patients with DLBCL, and showed no difference in OS using propensity-score weighted Cox regression models (Odejide et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…This study was risk-adapted based on a stage-modified IPI and interim positron emission tomography (PET) after 4 cycles and found that, overall, combined modality therapy was not significantly superior to R-CHOP alone in patients achieving early PET negativity (Lamy et al, 2014). Several retrospective analyses have reported conflicting results of the comparative effectiveness of short-course immunochemotherapy or extended-course immunochemotherapy with or without IFRT in patients treated with R-CHOP (Phan et al, 2010;Terada et al, 2012;Tomita et al, 2013;Odejide et al, 2015).…”
mentioning
confidence: 99%
“…The decision to include patients treated with combined modality therapy and chemoimmunotherapy was based on the weight of published evidence showing no difference in outcomes in the rituximab era. 43,44 Although these studies are mostly retrospective, Lamy et al demonstrated, in a prospective randomized study of nonbulky stage I/II DLBCL, that patients who achieved a negative interim positron emission tomography could be managed with no RT without compromising disease control. 45 Second, in this study we used the Hans algorithm to assign COO.…”
Section: Discussionmentioning
confidence: 99%